Impact of Incretin-Based Therapies on Adipokines and Adiponectin - Habib Yaribeygi; Mina Maleki; Stephen L. Atkin; Tannaz Jamialahmadi; Amirhossein Sahebkar (Journal of Diabetes Research)
Adipokines are a family of hormones and cytokines with both pro- and anti-inflammatory effects released into the circulation to exert their hormonal effects. Adipokines are closely involved in most metabolic pathways and play an important modulatory role in lipid and carbohydrate homeostasis as they are involved in the pathophysiology of most metabolic disorders. Incretin-based therapy is a newly introduced class of antidiabetic drugs that restores euglycemia through several cellular processes; however, its effect on adipokines expression/secretion is not fully understood. In this review, we propose that incretin-based therapy may function through adipokine modulation that may result in pharmacologic properties beyond their direct antidiabetic effects, resulting in better management of diabetes and diabetes-related complications.